Using ggtree to Visualize Data on Tree‐Like Structures. Issue 1 (5th March 2020) - Yu, Guangchuang
Abstract: Ggtree is an R/Bioconductor package for visualizing tree‐like structures and associated data. After 5 years of continual development, ggtree has been evolved as a package suite that contains treeio for tree data input and output, tidytree for tree data manipulation, and ggtree for tree data visualization. Ggtree was originally designed to work with phylogenetic trees, and has been expanded to support other tree‐like structures, which extends the application of ggtree to present tree data in other disciplines. This article contains five basic protocols describing how to visualize trees using the grammar of graphics syntax, how to visualize hierarchical clustering results with associated data, how to estimate bootstrap values and visualize the values on the tree, how to estimate continuous and discrete ancestral traits and visualize ancestral states on the tree, and how to visualize a multiple sequence alignment with a phylogenetic tree. The ggtree package is freely available at https://www.bioconductor.org/packages/ggtree . © 2020 by John Wiley & Sons, Inc. Basic Protocol 1 : Using grammar of graphics for visualizing trees Basic Protocol 2 : Visualizing hierarchical clustering using ggtree Basic Protocol 3 : Visualizing bootstrap values as symbolic points Basic Protocol 4 : Visualizing ancestral status Basic Protocol 5 : Visualizing a multiple sequence alignment with a phylogenetic tree